COVID-19 Adaptive Interventions: Implications for Wellbeing and Quality-of-Life - Ramkissoon, Haywantee (Frontiers in Psychology, 2022)
Social bonds may assist in cultivating a more positive attitude to life through commonly shared meanings about the COVID-19 pandemic. The key challenge however is how to foster social bonds meeting the changing demands in a post pandemic world. Yet, it is in the middle of a crisis that the conversation needs to start about how to strategically plan for the recovery. This is important not only in the current pandemic but also in a post pandemic world. Reinforcing or fostering new social bonds is likely to bring positive experiences. The latter is central to human health and wellbeing, and has potential to contribute greatly in enhancing people’s quality of life. This paper proposes a new conceptual framework suggesting the need for social bonding interventions in the SARS-COV-2 pandemic. This is an essential measure to manage the significant impacts on our global health services due to a decline in people’s mental health in addition to COVID-19 physical impacts. The paper discusses how social bonding interventions (psycho-socio, digital, and nature social bonding) can make people more resilient and be empowered psychologically, socially, and emotionally in the current challenging times. The conceptual framework posits that social bonding interventions can assist in maintaining better mental, physical, emotional and spiritual wellbeing and discusses how these wellbeing outcomes may be experienced post the pandemic. This is of relevance to governments, policy makers and healthcare professionals in delivering better health care and equipping people with coping mechanisms both throughout the pandemic and in the long run.